2007
DOI: 10.1029/2006jd008170
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic controls on summertime surface ozone in the northeastern United States

Abstract: The relationship between synoptic‐scale circulation patterns and surface ozone (O3) across the northeastern United States was investigated for summers 2000–2004. Observational data consisted of 1200 UT sea level pressure fields obtained from the National Centers for Environmental Prediction Global Final Analysis and O3 measurements from 474 Environmental Protection Agency and five AIRMAP monitoring sites. The five most common circulation patterns, or map types (I–V), were identified with a correlation‐based sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…10. The salient features in the observed average distribution corresponding to the five map types are very similar to those in Hegarty et al (2007) where the relationship was investigated between synoptic-scale circulation patterns and surface O 3 across the northeastern US for summers [2000][2001][2002][2003][2004]. We found that FNL1 and FNL5 depict the two stages of cold front passage over the Northeast with FNL1 preceding FNL5 ( Fig.…”
Section: Association Between Circulation and O 3 Distributionsupporting
confidence: 60%
See 1 more Smart Citation
“…10. The salient features in the observed average distribution corresponding to the five map types are very similar to those in Hegarty et al (2007) where the relationship was investigated between synoptic-scale circulation patterns and surface O 3 across the northeastern US for summers [2000][2001][2002][2003][2004]. We found that FNL1 and FNL5 depict the two stages of cold front passage over the Northeast with FNL1 preceding FNL5 ( Fig.…”
Section: Association Between Circulation and O 3 Distributionsupporting
confidence: 60%
“…The synoptic-scale circulation patterns were classified by applying the correlationbased map typing algorithm of Lund (1963) to the RCMS and NCEP FNL sea level pressure (SLP) fields. This technique has been successfully applied to synoptic classification of summertime circulation patterns over the northeastern United States (Hegarty et al, 2009(Hegarty et al, , 2007Hogrefe et al, 2004). The algorithm calculates a correlation coefficient between the grids representing scalar meteorological analysis fields over a given spatial domain at different times.…”
Section: Map Typingmentioning
confidence: 99%
“…This technique has been successfully applied to synoptic classification of summertime circulation patterns over the northeastern United States using the NCEP grids (Hegarty et al, 2007). In brief, the algorithm calculates a correlation coefficient between the grids representing scalar meteorological analysis fields over a given spatial domain at different times.…”
Section: Circulation Classificationmentioning
confidence: 99%
“…Hegarty et al, 2007 showed that certain circulation patterns over northeastern United States, identified with a correlation-based synoptic categorization technique, controlled summertime surface ozone. The 500 mb geopotential height as well as the zonal and meridional wind components are used as indicators for identifying the synoptic scale circulation differences between ECHAM and ERA simulations (Figs.…”
Section: Geopotential Height and Windmentioning
confidence: 99%